PSXIV-20 Ovine circulatory markers regulating the acute-phase response of variable stress responding sheep to LPS challenge. (8th October 2021) - Sharma, Ankita; Shandilya, Umesh K; Sullivan, Tianna; Naylor, Danielle; Cánovas, Angela; Mallard, Bonnie; Karrow, Niel
Abstract: Pathogens induce neuroendocrine-immune interactions in their hosts, which are a basis to overcome the microbial stressor. These interactions result in individual variation of the hypothalamic-pituitary-adrenal (HPA) axis response and could contribute to variable stress resiliency. In present study, a comprehensive set of circulatory markers was assessed in variable stress responding lambs selected from a population (n = 112) and categorized based on cortisol levels as high (HSR, 336.2 ±27.9 nmol/L, n =12), middle (MSR, 147.3 ±9.5 nmol/L, n =12) and low (LSR, 32.1 ±10.4 nmol/L, n =12) responding phenotypes post LPS challenge (400 ng/kg iv). Blood was collected from the jugular vein at 0 (pre-) and 4 hrs post-LPS challenge to monitor changes in serum with a panel of 15 pro- and anti-inflammatory cytokines and chemokines and 84 miRNAs, and white blood cell (WBC) populations. The HSR had the strongest fever and pro-inflammatory IL-6, IFN-γ cytokine responses compared to MSR and LSR. HSR and MSR had stronger anti-inflammatory IL-10 cytokine and CCL2 chemokine responses than LSR. WBC counts changed between 0 and 4 hrs; however, no differences were detected among the variable stress response groups. Three miRNAs, oar-miR-485-5p (+3.82 folds), oar-miR-1193-5p (+2.43 folds) and oar-miR-3957-5p (+3.14 folds) were significantly (P < 0.05) upregulated, and seven miRNAs, oar-miR-376b-3p (-6.6 fold), oar-miR-376c-3p (3.5 folds), oar-miR-411b-5p (-11.69 folds), (oar-miR-376a-3p (-2.28 fold), oar-miR-376b-3p (-6.08 folds), oar-miR-376c-3p (-2.62 folds), oar-miR-381-3p (-3.85 folds) were downregulated (P < 0.05) in HSR compared to LSR and MSR. Functional analysis of miRNAs revealed their roles in activating TGF-beta signalling, Cytokine receptor interaction and Thyroid signalling pathways in HSR phenotypes indicating a hyper-induced acute-phase response. In summary, these results indicate variation in the acute-phase response to stress, and some of these markers could be used as stress biomarkers. Further investigation is warranted to understand the plausible association of cortisol phenotype with other important traits.